Implementasi Kebijakan Pengadaan Barang Dan Jasa Pemerintah Dalam Pembangunan Ibu Kota Nusantara (IKN) - Wahyuni, Hasti (LPPM Universitas Putera Batam, 2024)
National development, which includes the development of the capital city of Nusantara, really requires important aspects such as the procurement of goods and services. Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah (LKPP) has collaborated with the IKN Authority in an effort to accelerate the economic transformation process and to achieve the vision of advanced Indonesia 2045 in IKN development. This paper aims to analyze the implementation of government goods and services procurement policies in the National Capital (IKN) Nusantara development project in East Kalimantan. This research is seen from the perspective of political economic theory of development. The type of research is qualitative research and is descriptive using library study data collection techniques. The research results show that the collaboration between LKPP and the IKN Authority is going well and able to speed up the IKN development process. LKPP as the only official government institution in terms of providing goods/services through its rules and policies has succeeded in carrying out its duties and authority as an institution that assists the process of procuring government goods and services by showing significant progress in IKN development. This can be seen from the ongoing development of IKN to create a national capital that reflects the nation's modern identity and international standard